Serum concentrations of l-arginine and l-homoarginine in male patients with intermittent claudication: A cross-sectional and prospective investigation in the CAVASIC Study. Issue 2 (April 2015) - Vogl, Lena; Pohlhammer, Johannes; Meinitzer, Andreas; Rantner, Barbara; Stadler, Marietta; Peric, Slobodan; Hammerer-Lercher, Angelika; Klein-Weigel, Peter; Fraedrich, Gustav; Kronenberg, Florian; Kollerits, Barbara
Abstract: Background: High serum concentrations of l -arginine and l -homoarginine increase nitric oxide (NO) availability and thereby improve endothelial function. Information about the association of these markers with peripheral arterial disease (PAD) and related outcomes is sparse. Methods: l -arginine, its metabolites and l -homoarginine were analyzed in the CAVASIC Study including 232 male patients diagnosed with intermittent claudication and 246 age- and diabetes-matched controls. After the baseline investigation PAD patients were prospectively followed (median 7 years). The association of these markers with symptomatic PAD at baseline, incident cardiovascular events and all-cause mortality was assessed. Results: At baseline each increase of ln-l -homoarginine and l -arginine by one standard deviation was associated with symptomatic PAD: OR = 0.75, 95%CI 0.59–0.96, P = 0.02 and OR = 1.36, 95%CI 1.07–1.73, P = 0.01, respectively (both models adjusted for ln-CRP, GFR, HDL cholesterol, and current smoking). Only l -arginine remained significant after additional adjustment for ln-NT-proBNP and hs-cTnT: OR = 1.49, P = 0.002. In the Cox regression analysis elevated ln-l -homoarginine significantly reduced the risk to die (n = 38) even independent from ln-NT-proBNP and hs-cTnT: HR = 0.59, 95%CI 0.41–0.84, P = 0.004. l -arginine was significantly predicting incident cardiovascular events (n = 65): HR = 1.68, 95%CI 1.35–2.10, P < 0.001. Conclusions: This study in male patients with intermittent claudication and age- and diabetes-matched controls showed an association of l -homoarginine and l -arginine with PAD. During follow-up, l -arginine was associated with incident cardiovascular events probably due to its primary role in NO metabolism and impact on endothelial integrity. l -homoarginine was related to all-cause mortality implying a broader role in metabolic processes besides endothelial function. Highlights: l -homoarginine and l -arginine are associated with symptomatic PAD. l -homoarginine is associated with all-cause mortality and l -arginine with incident CVD. l -homoarginine and l -arginine show improved discriminative ability for outcomes at follow-up.